Biogenic polyamines and genital gonococcal infection: facts and hypotheses - T. I. Karpunina; L. Yu. Nesterova (Бюллетень сибирской медицины, 2020)
Genital gonorrhea is one of the most common sexually transmitted diseases with significant gender differences in its clinical course. Laboratory verification of the diagnosis is associated with great difficulties in the cultivation and identification of the pathogen. Moreover, the diagnosis of female gonorrhea is a serious problem due to mild symptoms of the disease. Currently, a promising trend in the diagnosis of inflammatory diseases of reproductive organs is biochemical analysis of vaginal and sperm fluids, which have a rich component composition. Biogenic polyamines can be synthesized by both pro- and eukaryotic cells. These polycations are present in semen and vaginal fluid and can have a significant effect on various cell structures and functions. In this regard, the qualitative and quantitative composition, the level and ratio of these components and their changes can have a diagnostic value for infections of the genital tract.The aim of the review was to analyze current information on the role of biogenic polyamines in the physiological and biochemical potential of Neisseria gonorrhoeae and their participation in the development of genital gonococcal infection, taking into account the influence of sexual differences and a number of related factors. Special attention was paid to the origin and possible functional role of polyamines in the genital tract of men and women. As a result, taking into account the spectrum, origin and ratio of polyamines in the corresponding fluids, we formulated a hypothesis: the manifestation of the process in case of infection in men is largely determined by the reactivity of eukaryotic cells, but not the metabolic activity of the microbiota of the reproductive tract. At the same time, the development of “female” gonorrhea is primarily determined by the state of the microbiocenosis of the cervical vaginal biotope.